2020
DOI: 10.1364/oe.403293
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the chromatic dispersion effect on the subcarrier wave QKD system

Abstract: In this paper we investigate the chromatic dispersion impact on the quantum key distribution system based on multi-mode weak coherent phase-coded states. We provide an asymptotic secure key rate estimation, taking into account error detection probability due to chromatic dispersion. We demonstrate numerically and experimentally that the effect of chromatic dispersion in an optical fiber without any compensation hinders the secret key distribution at a distance more than 53 km. Finally, we propose a modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The influence of chromatic dispersion on the DV-SCW system was investigated in [25]. There was shown that SCW QKD systems are prone to the influence of the chromatic dispersion.…”
Section: Dispersion Effects In the Scw Cv-qkdmentioning
confidence: 99%
See 3 more Smart Citations
“…The influence of chromatic dispersion on the DV-SCW system was investigated in [25]. There was shown that SCW QKD systems are prone to the influence of the chromatic dispersion.…”
Section: Dispersion Effects In the Scw Cv-qkdmentioning
confidence: 99%
“…One of the methods of mitigating the dispersion influence, proposed in [25], is to send only one half of the spectrum to the channel. In the case of QKD with coherent detection, one have to carry out classical heterodyning via spectral filter and beam splitter.…”
Section: Dispersion Effects In the Scw Cv-qkdmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a valid approximation if dispersion compensator is used on Alice's side. Otherwise the dispersion should be included into analysis at distances longer than 25 km [17].…”
Section: Chromatic Dispersionmentioning
confidence: 99%